Peran Ibu Kota Nusantara Sebagai Kota Sustainable Cities Dalam Mensejahterakan Masyarakat Indonesia - Roy Armansyah; Muhamad Auza Syam; Nabila Azahra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The capital city of Indonesia, which was previously located in DKI Jakarta, is now moved to The Nusantara Capital in the East Kalimantan region, due to economic conditions where DKI Jakarta and its surroundings are the center of everything, therefore the money circulation in DKI Jakarta reaches 70 % , this causes an imbalance between the population and the region which causes uneven development and welfare in Indonesia. This type of research uses empirical juridical legal research. This research uses two approaches, namely the statute approach, and the conceptual approach. To achieve SDGs goal 11 related to the sustainability of cities and settlements, the Ibu Kota Nusantara (IKN) needs to develop a minimum of 60% green land, renewable energy, and low carbon emissions. Building environmentally friendly infrastructure such as sidewalks, bicycle lanes, and public transportation with minimal carbon emissions The Nusantara Capital will be modified to achieve equitable development, the main focus of the Indonesian government in implementing the Nusantara Capital as equity and the welfare of the Indonesian people through an environmentally friendly economy in the long term without causing ecological scarcity or environmental risks for future generations By implementing a green economy, Indonesians are expected to enjoy the benefits of sustainable economic growth.